Antecedents to Haidilao Hot Pot Restaurant Consumer Loyalty in Bangkok - Fan, Hairui; Saengnoree, Amnuay; Siripongdee, Surapong (My University, 2024)
This study's objective was to develop a structural equation model (SEM) of factors influencing consumer loyalty at Bangkok's Haidilao Hot Pot (HHP) Chinese restaurants. The study focused on consumers who visited the Central World Mall and Central Rama 9 Mall branches at least once during June and July 2023. The researchers used stratified random sampling to collect 312 questionnaires from the consumers surveyed. The questionnaire's validity and reliability were ensured through expert evaluation and pilot testing, with Cronbach's alpha values ranging from 0.81 to 0.89. Data were collected via an online questionnaire in both Thai and English and assessed for content validity and reliability. The SEM path analysis was conducted using LISREL 9.10, while SPSS for Windows 21 was used for descriptive statistics. Results indicated that all SEM factors positively influenced consumer loyalty, explaining 63% of the variance. The three most significant factors were service innovation (0.79), service quality (0.64), and service satisfaction (0.61). This study extends the limited post-COVID-19 literature on the Asian food and service sector by validating a comprehensive model of consumer loyalty specific to Chinese hot pot restaurants. It highlights the essential nature of service innovation, quality, and satisfaction in fostering consumer loyalty. The findings provide valuable insights for restaurant industry practitioners, highlighting the need to invest in service innovation and maintain high service quality to enhance customer satisfaction and loyalty. These strategies are essential for sustainable growth and operational improvements.
Keywords: Chinese Cuisine; Food and Beverage Industry; Restaurant Service Innovation; Service Quality; Thailand